Performance assessment of a boundary layer ingesting distributed propulsion system at off-design - Goldberg, Chana; Nalianda, Devaiah; Pilidis, Pericles; Singh, Riti; Laskaridis, Panagiotis (AIAA, 2017)
As research on boundary layer ingesting aircraft concepts progresses, it becomes important to develop methods that may be used to model such propulsion systems not only at design point, but also over the full ight envelope. This research presents a methodology and framework for simulating the performance of boundary layer ingesting propulsion systems at o -design conditions. The method is intended for use as a preliminary design tool that may be used to explore the design space and identify design challenges or potential optimum con gurations. The method presented in this research enables the rapid analysis of novel BLI con gurations at a preliminary design stage. The method was applied to a case study of NASA's N3-X aircraft, a blended wing body concept with a distributed propulsor array ingesting the airframe boundary layer. The performance of two propulsor in the array was compare, one at the airframe centreline and one at the extreme edge of the array. Due to di erence in ow conditions, the centreline propulsor was shown to be more e cient at o -design than the end propulsor. However, this di erence in e ciency disappeared at sea level static where the boundary layer thickness is negligible and mass ow ratio is high. Di erence in thrust produce by the two propulsors was instead due their di erent sizes. Performance of the propulsor array as a whole was also presented both independently and including a link to a pair of turbogenerators to provide power. At o design, it was found that there was a discrepancy between the maximum power available from the turbogenerators at o -design operating points and that demanded by the propulsor array operating at 100% fan rotational speed. This discrepancy means that the propulsor array's performance is limited by the turbogenerators at o -design, particularly for low speed, low altitude operation.